Learning Methods for Islamic Religious Education in the Merdeka Curriculum - Maulisa, Maulisa; Sri Rahmawati, Eka; Zainuri, Habib (ISTIFHAM, 2024)
Islamic Religious Education plays an essential role in shaping the character and morals of students in Indonesia, especially in the context of the Merdeka Curriculum. The primary purpose of Islamic Religious Education is to guide students to understand and practice Islamic teachings as a guide to life. With a more interactive and flexible learning approach, the Merdeka Curriculum allows educators to develop methods relevant to the diversity of student's potential and needs. This research examines various effective learning methods in Islamic Religious Education, such as discussion, project-based learning, contextual, storytelling, and demonstration. Hopefully, these methods can increase students' motivation and understanding of Islamic teachings and create an engaging and applicable learning atmosphere. In addition, professional training for teachers is needed to ensure effective curriculum implementation. Thus, this research aims to explore best practices in Islamic Religious Education and provide valuable recommendations to improve the quality of learning so that students become knowledgeable and have good character and morals as the nation's next generation.